High time resolution observations of HF cross‐modulation within the D region ionosphere. Issue 10 (30th May 2013) - Langston, J.; Moore, R. C.
<x xml:space="preserve">Abstract</x> [1] High‐frequency cross‐modulation is employed to probe the D region ionosphere during HF heating experiments at the High‐frequency Active Auroral Research Program (HAARP) observatory. We have adapted Fejer's well‐known cross‐modulation probing method to determine the extent of ionospheric conductivity modification in the D region ionosphere with high (5 μsec) time resolution. We demonstrate that the method can be used to analyze D region conductivity changes produced by HF heating both during the initial stages of heating and under steady state conditions. The sequence of CW probe pulses used allow the separation of cross‐modulation effects that occur as the probe pulse propagates upward and downward through the heated region. We discuss how this probing technique can be applied to benefit ELF/VLF wave generation experiments and ionospheric irregularities experiments at higher altitudes. We demonstrate that large phase changes equivalent to Doppler shift velocities >60 km/s can be imposed on HF waves propagating through the heated D region ionosphere.